An evaluation of dietary natural zeolite or humic acid substances and sulfate water on nursery pig performance - Flohr, J.R.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 350 nursery pigs (PIC 1050 barrows, initially 21 d of age) were used in a 21-d study to determine the effects of high-sulfate water, dietary natural zeolite, and dietary humic substances on growth performance and fecal consistency of nursery pigs. Ten treatments were arranged as a 2 × 5 factorial with 2 water treatments (control or water with 2,000 ppm sodium sulfate) and 5 dietary treatments (control, 1 or 2% zeolite, 1% humic acid substance [HA], or 1% humic and fulvic acid blended substance [HFB]). Water treatments remained the same from d 0 to 21 and all diets were fed in 2 phases, with diets containing feed additives at the same inclusion rate in both phases. Phase 1 diets were fed in a pellet form from d 0 to 8 after weaning; Phase 2 diets were fed in meal form from d 8 to 21. Fecal samples were collected on d 5, 8, 15, and 21. These samples were visually assessed and scored on a scale of 1 to 5 to determine consistency of the fecal samples, then analyzed for DM.
Keywords: Swine; Nursery pig; Sulfate; Water; Zeolite; Humic substances